O gênero das políticas institucionais e das experiências pessoais de homens e mulheres, membros não casados, da Assembleia de Deus Taboão, Campo Taboão, Ministério Madureira - Ferreira, Daisy Mota (2020)
This research aimed to analyze the gender perspective as institutional policies of the Assembly of Deus Taboão, Ministério Madureira, in relation to its system of ecclesiastical organization that implies the civil status of its members, particularly of unmarried men and women, and the impact on that group's personal experiences. Our approach is based on the most recent theoretical discussions of this religious segment, defining for its ecclesiastical organization and the use of the traditional and religious family institution as an efficient mechanism of gender order, which sanctifies the spaces of power and delimits places for men and women of occupation normative. A research proposal was to verify the volumes and spaces that are allowed or not allowed by the Assembly of Deus Taboão, which imply in the civil status and coherence with the social roles of gender in the practical life of its members; and the impact on the personal experience of unmarried male and female members, identifying the extent to which they reproduce and / or subvert a gender order of religious discourses. The research methodology involves bibliographic research and qualitative analysis of semi-structured interviews with church members and leaders.